Doxycycline inhibits MMP-2 retinal activity and modulates the angiogenic process in vitro and in vivo - María Lina Formica; María Constanza Paz; María Constanza Paz; María Victoria Vaglienti; María Victoria Vaglienti; Paula Virginia Subirada; Paula Virginia Subirada; Yamila Fernández; Yamila Fernández; Mariana Belén Joray; José Domingo Luna; Pablo Federico Barcelona; et al. (Frontiers in Cell and Developmental Biology)
IntroductionVascular endothelial growth factor (VEGF) inhibition is currently the first-line therapy for various retinal vascular disorders, however there is a strong need to develop novel therapies to target other molecules involved in the angiogenic process. In addition to well-known antibiotic properties, Doxycycline (DXC) has versatile non-antibiotic properties, therefore, our goal was to evaluate the effect of DXC on matrix metalloproteinase-2 (MMP-2) as a potential therapeutic alternative for retinal neovascularization (NV), using vascular and glial cells and the oxygen-induced retinopathy (OIR) mouse model.MethodsMGC and BAEC viability under DXC treatment was evaluated using an MTT assay. Changes of Pro MMP-2 and MMP-2 activity were measured by gelatin zymography assay in MIO-M1 cells incubated with DXC under normoxia and hypoxic conditions. VEGF-induced angiogenesis was assessed by tube formation assay in BAEC incubated with DXC for 24 h C57BL/6 mice exposed to OIR model, were intravitreally injected with a single dose of DXC at post-natal day (P)12 and retinas evaluated at P17.ResultsDXC significantly decreased pro MMP-2 and MMP-2 activity in MIO-M1 supernatants and increased hypoxic-induced mRNA expression of pigmentary epithelium-derived factor (PEDF). Moreover, DXC inhibited the VEGF-induced tube formation in endothelial cells. A single intraocular administration of DXC at postnatal day (P) 12 showed a significant decrease of pro MMP-2 and MMP-2 activity together with a reduced NV and vaso-obliteration in P17 mouse retinas of OIR eyes, while no significant difference was observed neither in MMP-2 nor in VEGF protein expression.DiscussionOur results lead to propose a possible DXC mechanism for inhibition of angiogenesis through the modulation of MMPs involving the VEGF/PEDF balance. These findings underscore the potential repositioning of DXC as a new possibility for treating ocular proliferative diseases.